A Review of Ed-Tech Sector in India - Chandni J. Vidani; Abhishek Bansal; Shreyas Pophalkar (International Journal of Managemen Analytics (IJMA), 2023)
This qualitative research paper aims to provide a comprehensive review of the Ed-tech sector in India by examining its current state, identifying key trends, and exploring the factors contributing to its growth and challenges. It investigates the diverse range of educational technologies being employed, including online platforms, mobile applications, virtual classrooms, and adaptive learning systems. The research critically examines the effectiveness and impact of these technologies on teaching and learning outcomes, as well as their influence on student engagement, accessibility, and equity. This research delves into the factors driving the growth of the Ed-tech sector in India, such as increasing smartphone penetration, improved internet connectivity, favorable government initiatives, and changing attitudes towards online learning. It also investigates the challenges faced by the sector, such as the digital divide, inadequate teacher training, concerns regarding data privacy and security, and the need for regulatory frameworks. It examines their strategies, business models, and partnerships, highlighting successful practices and lessons learned. By providing an in-depth analysis of the Ed-tech sector in India, this research paper offers valuable insights for policymakers, educators, investors, and stakeholders in the field of education. The outcomes of the study entail to the previous literature vis Ed-tech, helping to inform future initiatives, policies, and investments in the Indian education system